Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2500/ajra.2016.30.4325
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis, Endothelial Dysfunction, and Atherosclerosis

Abstract: CRS is associated with ED and atherosclerosis, as indicated by decreased FMD and increased CIMT in patients with CRS. Further studies are necessary to identify the exact pathophysiologic mechanisms responsible for our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Interestingly, nearly all the comorbidities considering in the current study, mainly the vascular and inflammatory diseases, were significantly prevalent in the surgery-indicated CRS population. The findings further supported the inflammatory nature of CRS and the relationship between CRS and metabolic syndrome, cardiovascular disease, and impaired pulmonary function that proven in previous studies [47,48,49,50,51]. Moreover, the CRS is related to the development of keratopathy according to a previous study using the same database [52] that corresponds to the distribution of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, nearly all the comorbidities considering in the current study, mainly the vascular and inflammatory diseases, were significantly prevalent in the surgery-indicated CRS population. The findings further supported the inflammatory nature of CRS and the relationship between CRS and metabolic syndrome, cardiovascular disease, and impaired pulmonary function that proven in previous studies [47,48,49,50,51]. Moreover, the CRS is related to the development of keratopathy according to a previous study using the same database [52] that corresponds to the distribution of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Increased pro-inflammatory markers and oxidative stress occurs in adipose tissues are the two factors that may play a key role in the incidence of metabolic-related comorbidities among patients with metabolic disorders [ 1 ]. Increased chronic inflammation is associated with increased risk of metabolic disorders, including type 2 diabetes mellitus (T2DM) [ 2 ] and arteriosclerosis, endothelial dysfunction, vascular calcification, increased activity of metalloproteinases, oxidative damage, and degradation of collagen [ 3 5 ]. It was reported that metabolic syndrome (MetS ) is associated with a 2-fold increased risk of cardiovascular disease (CVD) over the next 5 to 10 years [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of looking for a relationship between nasal disease and endothelial dysfunction has already been considered in a recent study by Elcioglu et al [30]. Indeed, they have…”
Section: Discussionmentioning
confidence: 97%